2017
DOI: 10.1021/acsami.7b01183
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hole Transporting Layer on the Thermal Stability of Inverted Organic Photovoltaics Using Accelerated-Heat Lifetime Protocols

Abstract: High power conversion efficiency (PCE) inverted organic photovoltaics (OPVs) usually use thermally evaporated MoO3 as a hole transporting layer (HTL). Despite the high PCE values reported, stability investigations are still limited and the exact degradation mechanisms of inverted OPVs using thermally evaporated MoO3 HTL remain unclear under different environmental stress factors. In this study, we monitor the accelerated lifetime performance under the ISOS-D-2 protocol (heat conditions 65 °C) of nonencapsulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Because of the complexity of this material, a clear understanding of the stability is lacking, and different interpretations are summoned, but it is clear that from this point of view molybdenum oxide is not an issue‐free material. For example, using three different donor:fullerene systems, Hermerschmidt et al have shown that inverted polymer solar cells with e‐MoO x undergo a photovoltaic performance decay in air and under accelerated ageing conditions ( T = 65 °C). They have attributed this behavior to a degradation of the active layer/e‐MoO x interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the complexity of this material, a clear understanding of the stability is lacking, and different interpretations are summoned, but it is clear that from this point of view molybdenum oxide is not an issue‐free material. For example, using three different donor:fullerene systems, Hermerschmidt et al have shown that inverted polymer solar cells with e‐MoO x undergo a photovoltaic performance decay in air and under accelerated ageing conditions ( T = 65 °C). They have attributed this behavior to a degradation of the active layer/e‐MoO x interface.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of photovoltaic performances, P3HT:PCBM active blend is quite tolerant to any buffer layer, but other materials are not, as it will be shown also in the present work. As a matter of fact, direct comparisons of e‐MoO x and PEDOT:PSS are seldom reported in the literature, but in those cases, the PCEs drop dramatically (Table ) . One of the possible reasons could be the unsuitable work function of PEDOT:PSS (about 5–5.2 eV).…”
Section: Introductionmentioning
confidence: 99%
“…The SM5‐based device maintained over 55% of its initial PCE after 1200 h of thermal treatment, whereas that of the PEDOT:PSS‐based device continuously dropped below 25% for the same measurement period. The devices were also tested under thermal treatment at 85 °C in relative humidity of 20% in average, following the environmental conditions adopted by the ISOS‐D‐2 protocol . Both the PCE of PEDOT:PSS‐ and SM‐based devices dropped rapidly within 50 h (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…7b) is referred to as burn-in 21,22 , which is a signature of light induced degradation 24 . This burn-in has been demonstrated to be related to the photoinduced dimerization of fullerenes within the active layer 50,51 . The larger drop for CFO-OSC is attributed to the higher absolute J sc initial value.…”
Section: Isos-o-1 Testmentioning
confidence: 97%